Management of Cardiovascular Disease Patients with Periodontitis Requiring Dental Treatment - A KAP Study among Dental Students - Anal R. Trivedi; Shalini S. Gupta; Vasumati I. Patel; Rutvik H. Trivedi; Neeta V. Bhavsar; Chintal K. Vyas; Hiral A. Parikh (Wolters Kluwer Medknow Publications, 2024)
Background: It is frequently observed that dental students require so many consents to manage medically compromised patients, especially cardiovascular patients with periodontitis requiring dental treatment. Aims and Objectives: The present study aimed to assess the dental students' knowledge, attitudes, and practices regarding the management of cardiovascular disease (CVD) patients with periodontitis requiring dental treatment. Material and Methods: The cross-sectional study was conducted among 611 dental undergraduate and postgraduate students (branches of Periodontology, Oral and Maxillofacial Surgery, Oral Medicine and Radiology, Endodontics, Prosthodontics, and Public Health and Dentistry) of central Gujrat. Self-administered structured questionnaires with 23 questions were distributed in pen-and-paper physical format. Statistical analysis for descriptive statistics like frequency, percentage, mean, standard deviation, confidence interval, one-way analysis of variance, post hoc test for multiple comparisons, Fisher's exact test, and Pearson's correlation has been done by MS Excel and STATA/IC-13. Results: As per the post hoc test, both groups of students have significantly different knowledge (-4.20210*, P = 0.028) and their practices (0.68632, P = 0.968) but no significant difference between their attitudes (-6.22828, P = 0.089). According to the Pearson correlation test, a weak positive/no relationship between knowledge, attitudes, and practice is reported in both study groups. There is a weak positive relation between knowledge and attitudes (0.270) and between knowledge and practices (0.121), and a similar relationship between their attitudes and practices (0.172) was observed in both groups. Conclusion: Correct knowledge, attitudes, and practices regarding dental management of CVD patients with periodontitis can reduce medical consent to improve the treatment quality of dental students.